Lessons from the great recession at the crossroads of sustainability and recovery - Gurdgiev, Constantin T.; Leonard, Liam.; Gonzalez-Perez, Maria-Alejandra. (Bingley, U.K. : Emerald, 2016)
This volume examines global cases of environmental sustainability and economics in the context of nations from multi-disciplinary perspectives. This book analyses the problems faced globally as economies try to build a sustainable future in the aftermath of the'Great Recession', and the recent economic and financial crises.
Lessons from the Great Recession: At the Crossroads of Sustainability and Recovery examines global cases of environmental sustainability and economics in the context of nations from multi-disciplinary perspectives. The book discusses the high costs of decisions taken in response to the recent economic crises, which as a result have created a lack of investment in environmental and developmental considerations. This volume analyses the problems faced globally as economies try to build a sustainable future in the aftermath of the'Great Recession'. The book observes concepts of sustainability in the post-recession and post-bailout world around aspects such as Fiscal / economic / social sustainability; Financial sustainability (sector risks etc.); Environmental sustainability. Chapters scrutinise the relationships between nations and supra state agencies such as the UN, EU, IMF etc. in the context of economic crises.
Crisis contagion from advanced economies into BRIC: not as simple as in the old days / Constantin Gurdgiev, Barry Trueick -- Turning tigers into PIIGS: the role of leverage in the Irish economic collapse / Shaen Corbet -- Manhattan is not New York: the divergent import of the great recession and natural disasters on New York City's Five Boroughs / Carolyn E. Predmore, Lauren Trabold -- UNASUR-GRID: financing sustainable energy sovereignty with the Bank of the South / Tony Phillips -- On the effects of commodities prices on sustainable development: an opportunity? / Gustavo Canavire-Bacarreza, Maria Aristizabal-Ramirez -- Improving post-2015 development cooperation through donor support for inclusive business / Maria Alejandra Pineda-Escobar, Fabian Garzon Cuervo -- The great recession and emerging market firms: unpacking the divide between global and national level sustainability expectations / Luis Alfonso Dau, Elizabeth Maire Moore, Margaret Soto -- Global financial crisis and the emergence and maturing of socially responsible investments / Carolina Herrera-Cano, Maria Alejandra Gonzalez-Perez -- After the flood comes the tax: European road to financial transactions tax / Constantin Gurdgiev, Barry Murphy -- Networked social movements and the politics of mortgage: from the right to housing to the assault on institutions / Eva Alvarez de Andres, Patrik Zapata, Maria Jose Zapata Campos -- Solar eclipse: investment treaty arbitration and Spain's photovoltaic troubles / Ioannis Glinavos -- Capital for the twenty-first century: a response to'Capital in the Twenty-First Century' by Thomas Piketty / Amelia Correa, Romar Correa.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Development -- Sustainable Development; Environmental economics; Economic stabilization; Sustainable development; Environmental economics; Global Financial Crisis, 2008-2009.